The Urgency of Fiqh Rules in Islamic Civil Law - Khairil Azmi Nasution (International Journal Reglement & Society (IJRS), 2022)
The rules of fiqh have an important role in resolving legal issues that are not found in the texts of the Qur'an and Sunnah, including issues related to Islamic Civil Law. The rules of fiqh turned out to provide a concrete solution to the need for a method or method of finding the law (istinbath al-ahkam). In addition, the rules of fiqh also make it easier for us to master problems, civil issues that arise and develop in human life. This paper presents the urgency of fiqh rules in formulating Islamic civil law. This writing is carried out using a descriptive method through a rule relating to marriage, divorce, inheritance and wills